Community Driven Development: Community and Company Synergy in Developing Farmer Empowerment Programs in Kranjang Hamlet, Wayame Village, Teluk Ambon District, Ambon City - Khansa Nur Husna; Khairunnisa Diltha; Ahmad Tarmizi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The farmer empowerment program in Kranjang Hamlet is a community empowerment program that aims to improve farmers' welfare and maximize agricultural potential in Kranjang Hamlet. This program was initiated by PT Pertamina Patra Niaga SH C&T Integrated Terminal Wayame and is a form of implementation of corporate social and environmental responsibility. This program is run using a participatory rural appraisal where the community is the subject and main actor in the empowerment program. In its implementation, this program prioritizes the synergy between the community and the company in accordance with the community driven development. The qualitative results of the farmer empowerment program in Kranjang Hamlet can be seen as an example of a successful program because it involves the community in all stages of program planning, implementation, and evaluation.